Associations of sociodemographic, livelihood, maternal and infant factors with maternal emotional experiences during COVID-19 pandemic in Malaysia - Mohamad Nasri, Nuruljannah (2022)
Movement Controlled Order in Malaysia during COVID-19 has prompted many restrictions and changes in policies and management in public and government entities, including healthcare providers. As postpartum mothers are vulnerable, pandemic situations may have an impact on maternity and infant care, influencing maternal mental health. Therefore, this cross-sectional study aimed to assess the associations of sociodemographic characteristics, pandemic livelihood impact, birth and postnatal experiences, maternal activities, and infant feeding behaviours with maternal emotional experiences during the COVID-19 pandemic in Malaysia. An online survey was completed by 1449 mothers with ≤18 month’s infants from July 2020 to February 2021. The study information was disseminated through social media using convenience sampling. The majority of mothers were Malay (71.4%), attained bachelor degree (44.6%) and had monthly income <RM4000 (43.5%). Worried (54.7%), annoyed (48.1%), and tired (42.2%) were the top negative maternal emotions. Negative emotions and coping were emotional outcomes of principal component analysis of maternal experiences. Predictors of maternal negative emotions and coping were determined using multiple linear regression. Younger, more educated, rent-burdened, husbandunemployed, exercised, had postnatal care person, and experienced less evenly divided house chores predicted negative emotions (all p<.05). Conversely, positive predictors were mothers who received support on their well-being and feeding, had more time to focus on health, had infants sleeping less, and no infant behavioural change (all p<.05). Furthermore, mothers with a higher income, an unpaid leave partner, friend support, traditional postpartum care, more evenly divided house chores, and time to focus on health coped better (all p<.05). However, mothers who struggled to pay essentials predicted poor coping (p=.023). In conclusion, there were multiple negative and positive associations of sociodemographic, livelihood and mother-infant factors with maternal emotional experiences. Thus, early mental health screening during postnatal check-ups is recommended, and coping intervention should incorporate knowledge, skills, and support.